2001
DOI: 10.1002/etc.5620200521
|View full text |Cite
|
Sign up to set email alerts
|

Negative correlation between plasma thyroid hormone levels and chlorinated hydrocarbon levels accumulated in seals from the coast of Hokkaido, Japan

Abstract: Chlorinated hydrocarbon (CHC) levels in the blubber of larga seals (Phoca largha) and ribbon seals (Phoca fasciata) collected from the coastal waters of Hokkaido, Japan, were determined in order to assess the hormonal effects of CHC exposure in free-ranging pinnipeds. Plasma thyroid hormone levels, including total thyroxine (T4), free thyroxine (free T4), total triiodothyronine (T3), and free triiodothyronine (free T3), were also measured. Higher concentrations of polychlorinated biphenyl congeners (PCBs), dic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…Negative correlations between OCs and plasma T3 concentrations in gray seal pups of the present study are consistent with observations in Larga seals (Phoca larga) from Japanese waters, where plasma TT3 and FT3 concentrations correlated negatively with blubber PCB concentrations [9]. In ribbon seals (Phoca fasicata), also from Japanese waters, plasma TT3 levels decreased significantly with increased blubber PCB concentrations, whereas no such relationship was found between blubber PCBs and FT3 in this species [9]. Plasma TT4 and FT4 concentrations, however, were not affected by blubber PCB concentrations in either Larga or ribbon seals [9].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Negative correlations between OCs and plasma T3 concentrations in gray seal pups of the present study are consistent with observations in Larga seals (Phoca larga) from Japanese waters, where plasma TT3 and FT3 concentrations correlated negatively with blubber PCB concentrations [9]. In ribbon seals (Phoca fasicata), also from Japanese waters, plasma TT3 levels decreased significantly with increased blubber PCB concentrations, whereas no such relationship was found between blubber PCBs and FT3 in this species [9]. Plasma TT4 and FT4 concentrations, however, were not affected by blubber PCB concentrations in either Larga or ribbon seals [9].…”
Section: Discussionsupporting
confidence: 92%
“…Numerous studies have documented that OCs may affect thyroid hormone (TH) function and homeostasis in experimental animals, wildlife species, and humans (as reviewed in [1][2][3]). Several studies indicate that OCs also may affect TH function in seals [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Because many of these species also inhabit Arctic waters, I have chosen to include some of the main findings from these studies here. In ribbon seals ( Phoca fasicata ) from Japanese waters, TT 3 levels decreased significantly with increased blubber concentrations of PCB-170 and PCB-180, whereas no such relationship was found between blubber PCBs and FT 3 (Chiba et al 2001). In Larga seals ( Phoca largha ), also from Japanese waters, plasma TT 3 and FT 3 correlated negatively with blubber PCB concentrations, whereas no such relationships were found between blubber PCB concentrations and TT 4 and FT 4 in either Larga or ribbon seals (Chiba et al 2001).…”
Section: Endocrine Disruption In Arctic Marine Mammals and Seabirdsmentioning
confidence: 94%
“…Organochlorines like polychlorinated biphenyls (PCBs); p,p'-dichlorodiphenyltrichloroethane (p,p'-DDT); and its metabolite, p,p'-dichlorodiphenyldichloroethylene (p,p'-DDE) are part of a wide range of environmental contaminants suspected to interfere with endocrine functions in marine mammals (Aguilar & Borrel, 1995;Bruhn et al, 1995;Brouwer et al, 1999;Gregory & Cyr, 2003). Studies performed on laboratory and domestic animals as well as marine mammals showed a correlation between the intake of organochlorines and changes in hormone levels (Byrne et al, 1987;Brouwer et al, 1989;Chiba et al, 2001;Skaare et al, 2001;Haave et al, 2003;Braathen et al, 2004;Oskam et al, 2004;Sørmo et al, 2005;Zimmer et al, 2009). Organochlorines are lipophilic compounds.…”
Section: Introductionmentioning
confidence: 99%